HUBUNGAN DUKUNGAN KELUARGA DENGAN PROSES RUJUKAN DINI BERENCANA DI WILAYAH KERJA PUSKESMAS TEMPEH KABUPATEN LUMAJANG - Desti, Elvira Vrecilia; Rohmatin, Homsiatur; Farianingsih, Farianingsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
One of the weaknesses of health services is the implementation of referrals that are not fast and precise. The referral is not a deficiency but a high responsibility and prioritizes the needs of the community. This study aimed to analyze the correlation between family support and the Early Referral Process for Planning in the Working Area of the Tempeh Health Center, Lumajang. The research method used an observational study with a cross-sectional approach. all pathological pregnant women in the working area of the Tempeh Public Health Center, a total of 30 respondents were taken by accidental sampling technique, the test used was Chi-Square. almost half of the respondents with good family support almost half wanted to do RDB with a total of 8 people (26.7%), respondents with sufficient support almost half wanted to do RDB with a total of 10 people (33.3%) and those with less support did not want to be RDB as many as 3 people (10%). The results of the analysis using SPSS obtained p value = 0.034 < α = 0.05. The conclusion is that there is a correlation between family support and the early referral planning process in the working area of the Tempeh Health Center, Lumajang. Family support is very important in the early referral process. Most high-risk patients still rely on family support in deciding to make early referrals to hospitals.